A semiótica do burlesco: o figurino e a construção da personagem - Perez, Mirela Silva (2020)
Burlesque dance as a form of expression of individuality and female empowerment, being the costume, the result of sign elements of glamor, fetish and deconstruction, the vehicle through which this individuality is expressed. The objective of this research will be to understand the role of Burlesque in the woman's self-affirmation process, and the importance of the costume in the characterization of the female individuality, an idea that will be proven through the analysis of the characters (as well as their numbers and costumes) created by the Burlesque dancers of the São Paulo’s art scene. The analyzes will be carried out based on Peirce semiotics using the repertoire acquired throughout the initial chapters, which have as their theme the pillars of the development of Burlesque - History, Glamor, Fetish and Deconstruction. Concluding that the Neoburlesque as a source of generalized diversity proposes new definitions of the feminine, and the costume is a constitutive vector of this identity